Micro-arc oxidation film layer capable of regulating and controlling generation of cuprous oxide and preparation method of micro-arc oxidation film layer

The microarc oxidation process forms a film layer of Cu2O/CuO mixture on the surface of metal or alloy, which solves the problem of easy oxidation of copper-based sterilization materials in humid environments, and achieves the maintenance of efficient sterilization performance and simplification of the process.

CN119507002AInactive Publication Date: 2025-02-25DALIAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411552595.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing copper-based sterilization materials are prone to oxidation in humid environments, resulting in reduced sterilization effect, and complex preparation process, high energy consumption, low product purity and difficult morphology control.

Method used

The film layer is formed on the surface of metal or alloy through a microarc oxidation process, and the voltage control is used to achieve the valence-adjustable transition of copper oxides, and a mixture of Cu2O/CuO is generated, optimizing the antibacterial, electrocatalytic and mechanical properties of the film layer.

Benefits of technology

It realizes stable and efficient sterilization performance in humid environments, simplifies the preparation process, and improves the antibacterial, electrocatalytic and mechanical properties of the membrane layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005115470600000011
    Figure HDA0005115470600000011
  • Figure HDA0005115470600000012
    Figure HDA0005115470600000012
  • Figure HDA0005115470600000021
    Figure HDA0005115470600000021
Patent Text Reader

Abstract

The invention relates to the technical field of micro-arc oxidation treatment, in particular to a micro-arc oxidation film layer capable of regulating and controlling generation of cuprous oxide and a preparation method of the micro-arc oxidation film layer. A film layer is formed on the surface of metal or alloy through micro-arc oxidation, a porous structure of the film layer is filled with a mixture of CuO and Cu2O, and the Cu2O is obtained through high-temperature decomposition at 700-2000 DEG C in the micro-arc oxidation discharge process and reduction reaction in the negative process. The cuprous oxide is fixed in the micro-arc oxidation film layer, the cuprous oxide is not easy to oxidize, and the sterilization and bacteriostasis effects of the cuprous oxide are ensured, so that the problem that the sterilization and bacteriostasis effects are reduced due to the fact that the cuprous oxide in a traditional copper-based sterilization material is easy to oxidize into copper oxide in a humid environment is solved. Meanwhile, it is found that in the micro-arc oxidation process, the relative content of Cu2O / CuO in the film layer can be effectively regulated and controlled by changing the positive voltage and the negative voltage and changing the valence state of copper oxidation, and different antibacterial requirements are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of micro-arc oxidation treatment, and in particular to a micro-arc oxidation film layer capable of controlling the generation of cuprous oxide and a preparation method thereof. Background Art

[0002] Copper (Cu) and its compounds are widely used in many fields due to their natural bactericidal properties. + ) has a significantly better bactericidal effect than divalent copper ions (Cu 2+ ), which is mainly attributed to the higher redox potential and stronger ability of monovalent copper ions to penetrate cell membranes. However, existing copper-based bactericidal materials have some limitations in practical applications.

[0003] First, although traditional copper-based bactericidal materials, such as cuprous oxide (Cu2O), show good bactericidal properties in a dry environment, they are easily oxidized in humid air and gradually converted into copper oxide (CuO), thereby reducing their bactericidal effect. Secondly, the existing preparation methods of cuprous oxide have problems such as high equipment requirements, high energy consumption, harsh reaction conditions, low product purity and difficulty in morphology control.

[0004] Therefore, developing a copper-based material that can remain stable in a humid environment and has efficient bactericidal performance, while simplifying its preparation process, has become an important direction of current research. The present invention aims to solve the above problems and provide a preparation method of a new copper-based bactericidal material to meet the needs of practical applications. Summary of the invention

[0005] The purpose of the present invention is to provide a novel copper-based bactericidal material and a preparation method thereof to meet the needs in practical applications. The preparation method of the present invention realizes the controllable valence state transformation of copper in the film layer through voltage control, reasonable electrolyte system design and optimization of micro-arc oxidation process conditions, thereby giving the film layer excellent antibacterial properties, electrocatalytic properties and mechanical properties.

[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical solutions:

[0007] The present invention provides a micro-arc oxidation film layer capable of being regulated to generate cuprous oxide. The micro-arc oxidation film layer capable of being regulated to generate cuprous oxide is formed on a metal or alloy surface by micro-arc oxidation. A mixture of CuO and Cu2O is filled in a porous structure of the film layer. The Cu2O is obtained by high-temperature decomposition at 700°C to 2000°C during micro-arc oxidation discharge and a reduction reaction in a negative process.

[0008] In the above technical solution, further, the content of CuO and Cu2O is regulated by controlling the forward voltage and the negative voltage during the micro-arc oxidation process.

[0009] In the above technical solution, further, the forward voltage is 200V-700V to generate Cu2O phase; the negative voltage is 50V-150V to promote the reduction of CuO to Cu2O and increase the relative content of Cu2O; preferably, the forward voltage is 500V-600V, and the negative voltage is 90V-110V.

[0010] By adjusting the applied voltage, the valence state of copper oxide can be effectively controlled. Specifically, the influence of forward voltage: During the micro-arc oxidation process, the forward voltage mainly controls the intensity and temperature of the oxidation reaction on the anode surface. High temperature is conducive to the decomposition of CuO into Cu2O, which controls the valence state of copper oxide. + and Cu2 + By adjusting the specific value of the forward voltage, copper oxides of different valence states can be formed on the anode surface. In the forward voltage range of 200V to 700V, it is easier to form Cu + valence state, thereby generating Cu2O phase in the film layer. Effect of negative voltage: Negative voltage mainly promotes the reduction reaction. Under negative voltage conditions in the range of 50V to 100V, the reaction of CuO reduction to Cu2O is conducive to occur, and the relative content of Cu2O increases. Under negative voltage conditions in the range of 100 to 150V, the reduction intensity increases, so that Cu2O is reduced to elemental Cu, and the relative content of Cu2O decreases.

[0011] In order to obtain a film layer with high Cu2O / CuO, the present invention adopts the following voltage combination: forward voltage is 200V-700V, negative voltage is 50V-150V, preferably forward voltage: 500V-600V, negative voltage: 90V-110V.

[0012] In the above technical solution, further, the metal or alloy includes aluminum, magnesium, titanium, aluminum alloy, magnesium alloy, titanium alloy; preferably, the aluminum alloy is 2024 aluminum alloy, 7075 aluminum alloy or 6061 aluminum alloy.

[0013] In the above technical solution, further, the film layer has a thickness of 10 μm to 70 μm.

[0014] The present invention also provides a preparation method of the aforementioned Cu2O copper-based material, wherein the preparation method comprises treating a metal or aluminum alloy substrate by micro-arc oxidation to form a film layer on the surface of the substrate; the electrolyte of the micro-arc oxidation comprises water, alkaline hydroxide, silicate, and nano CuO particles; the micro-arc oxidation uses a metal or aluminum alloy substrate as an anode and a stainless steel container as a cathode, and uses a pulsed AC power supply for treatment, with a forward voltage of 200V-700V, a negative voltage of 50-150V, a pulse width of 200ms-4000ms, an interval between pulses of 200ms-1000ms, a temperature of 20°C-85°C, and a treatment time of 2min-30min; preferably, the forward voltage is 500V-600V, the negative voltage is 90V-110V, the pulse width is 1000ms-3000ms, and the interval between pulses is 250ms-750ms.

[0015] In the above technical solution, further, the mass concentration of alkaline hydroxide is 1g / L-15g / L, the mass concentration of silicate is 1g / L-25g / L, and the mass concentration of nano-CuO particles is 0.1g / L-20g / L; the alkaline hydroxide includes one or more of potassium hydroxide and sodium hydroxide; the silicate includes one or more of sodium silicate and potassium silicate; the nano-copper oxide particle size is 1nm-100nm; preferably, the hydroxide concentration is 1-3g / L, the silicate concentration is 2-5g / L, the nano-CuO particle concentration is 8-15g / L; the nano-copper oxide particle size is 40nm-60nm; the pH value of the electrolyte is 8-14.

[0016] In the above technical solution, further, the power supply is a bipolar pulse power supply, which adopts a unidirectional mode or a unidirectional first and then bidirectional working mode.

[0017] In the above technical solution, further, the aluminum alloy workpiece is polished, cleaned, and dried before micro-arc oxidation treatment, and is specifically polished with 2000-mesh metallographic sandpaper. After polishing, the substrate is cleaned with deionized water and dried at room temperature.

[0018] The present invention also provides a method for improving the bactericidal and antibacterial stability of Cu2O. The above-mentioned preparation method is used to form a film layer on the surface of a substrate, and the porous structure of the film layer is filled with a mixture of CuO and Cu2O.

[0019] The present invention also provides a method for regulating the valence state of copper oxide in a micro-arc oxidation film layer, which adopts the above-mentioned preparation method and controls the valence state of copper oxide by controlling the forward voltage and the negative voltage, thereby regulating the relative content of Cu2O / CuO.

[0020] The present invention also provides the use of the aforementioned Cu2O copper-based material in microsurgical instrument materials, orthopedic external fixator materials, and thoracic surgical instrument materials.

[0021] The relative content of Cu2O / CuO in the micro-arc oxidation film layer prepared by the present invention reaches 0.17-12.87, the hardness of the film layer reaches 300Hv-1500Hv, and the roughness (Ra) reaches 0.213-3.495.

[0022] Beneficial effects of the present invention:

[0023] The present invention proposes for the first time a micro-arc oxidation film layer capable of controlling the generation of cuprous oxide and a preparation method thereof. The film layer is formed on the surface of a metal or alloy by a micro-arc oxidation process, and cuprous oxide is fixed in the film layer and is not easily oxidized, thereby ensuring the bactericidal and antibacterial effect of cuprous oxide, thereby solving the problem that cuprous oxide (Cu2O) in traditional copper-based bactericidal materials is easily oxidized into cupric oxide (CuO) in a humid environment, resulting in reduced bactericidal and antibacterial effects. At the same time, the present invention finds that in the micro-arc oxidation process, by changing the forward voltage and the negative voltage and changing the valence state of copper oxidation, the relative content of Cu2O / CuO in the film layer can be effectively controlled to meet different antibacterial requirements.

[0024] The micro-arc oxidation treatment process of the micro-arc oxidation film layer capable of controlling the generation of cuprous oxide and the preparation method thereof is simple, and the workpiece pretreatment only requires deionized water rinsing, followed by the preparation of a working fluid, and subsequently only requires micro-arc oxidation discharge treatment and post-treatment, a total of four steps, and the working fluid does not require complex components. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Flow chart of the preparation of micro-arc oxidation film.

[0026] Figure 2 XPS analysis of Cu element in micro-arc oxidation film.

[0027] Figure 3 Cross-sectional morphology of the film layer of Example 5.

[0028] Figure 4 A picture showing that a complete film layer was not formed in Example 8. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited in any way.

[0030] The experimental methods adopted are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.

[0031] Example 1

[0032] The Cu2O copper-based material was prepared using 2024 aluminum alloy as the substrate: the polished and cleaned aluminum alloy sheet was used as the anode, and the stainless steel container was used as the cathode. A pulsed AC power supply was used for micro-arc oxidation treatment in a unidirectional and then bidirectional manner. The anode of the aluminum alloy workpiece was immersed in the working liquid, and then bipolar pulse electricity was applied to both the cathode and the anode, with a forward voltage of 700V, a negative voltage of 80V, a pulse width of 4000ms, and an interval of 500. The Cu2O copper-based material was obtained after treatment for 20 minutes at a temperature below 85°C.

[0033] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the concentration of sodium hydroxide in the working solution is 1 g / L, the concentration of sodium silicate is 8 g / L and the concentration of nano copper oxide is 20 g / L.

[0034] The aluminum alloy is 2024 aluminum alloy, and the size is 20 mm×20 mm×2 mm. The stainless steel container is 316 stainless steel.

[0035] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed to form a colloid.

[0036] The initial water temperature in this embodiment is 20°C.

[0037] The relative content of Cu2O / CuO in the micro-arc oxidation film layer for changing the copper valence state prepared in this embodiment reaches 4.25, the hardness of the film layer reaches 1500Hv, the roughness (Ra) reaches 3.495, and the thickness of the film layer is 50μm to 60μm.

[0038] Example 2

[0039] The Cu2O copper-based material was prepared using 7075 aluminum alloy as the substrate: the polished and cleaned aluminum alloy sheet was used as the anode, and the stainless steel container was used as the cathode. A pulsed AC power supply was used for micro-arc oxidation treatment in a unidirectional and then bidirectional manner. The anode of the aluminum alloy workpiece was immersed in the working liquid, and then bipolar pulse electricity was applied to both the cathode and the anode, with a forward voltage of 500V, a negative voltage of 150V, a pulse width of 2000ms, and a pulse interval of 200. The Cu2O copper-based material was obtained by treating it for 30 minutes at a temperature below 85°C.

[0040] The working solution is a mixture of deionized water, potassium hydroxide, sodium silicate and nano copper oxide particles; the concentration of alkaline sodium hydroxide in the working solution is 2 g / L, the concentration of sodium silicate is 25 g / L and the concentration of nano copper oxide is 6 g / L.

[0041] The aluminum alloy is 7075 aluminum alloy, and the size is 20 mm×40 mm×2 mm.

[0042] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed to form a colloid.

[0043] The initial water temperature in this embodiment is 20°C.

[0044] The relative content of Cu2O / CuO in the micro-arc oxidation film layer for changing the copper valence state prepared in this embodiment reaches 4.56, the hardness of the film layer reaches 898Hv, the roughness (Ra) reaches 0.855, and the thickness of the film layer is 50μm to 70μm.

[0045] Example 3

[0046] The Cu2O copper-based material was prepared using 2024 aluminum alloy as the substrate: the polished and cleaned aluminum alloy sheet was used as the anode, and the stainless steel container was used as the cathode. A pulsed AC power supply was used to perform a unidirectional and then bidirectional micro-arc oxidation treatment. The anode of the aluminum alloy workpiece was immersed in the working liquid, and then bipolar pulse electricity was applied to both the cathode and the anode, with a forward voltage of 200V, a negative voltage of 80V, a pulse width of 200ms, and an interval of 500ms. The Cu2O copper-based material was obtained after the treatment for 20 minutes at a temperature above 20°C.

[0047] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the concentration of sodium hydroxide in the working solution is 2 g / L, the concentration of sodium silicate is 1 g / L and the concentration of nano copper oxide is 6 g / L.

[0048] The aluminum alloy is 2024 aluminum alloy, and the size is 20 mm×20 mm×2 mm.

[0049] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed to form a colloid.

[0050] The initial water temperature in this embodiment is 20°C.

[0051] The relative content of Cu2O / CuO in the micro-arc oxidation film layer for transforming the copper valence state prepared in this embodiment reaches 3.67, the hardness of the film layer reaches 359Hv, the roughness (Ra) reaches 2.226, and the thickness of the film layer is 20μm to 30μm.

[0052] Example 4

[0053] The Cu2O copper-based material was prepared using 6061 aluminum alloy as the substrate: the polished and cleaned aluminum alloy sheet was used as the anode, and the stainless steel container was used as the cathode. A pulsed AC power supply was used to perform a unidirectional and then bidirectional micro-arc oxidation treatment. The anode of the aluminum alloy workpiece was immersed in the working liquid, and then bipolar pulse electricity was applied to both the cathode and the anode, with a forward voltage of 560V, a negative voltage of 50V, a pulse width of 400ms, and an interval of 1000ms. The Cu2O copper-based material was obtained after the treatment for 2 minutes at a temperature above 20°C.

[0054] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the concentration of sodium hydroxide in the working solution is 15 g / L, the concentration of sodium silicate is 8 g / L and the concentration of nano copper oxide is 0.1 g / L.

[0055] The aluminum alloy is 6061 aluminum alloy, and the size is 20 mm×20 mm×2 mm.

[0056] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed to form a colloid.

[0057] The initial water temperature in this embodiment is 20°C.

[0058] The relative content of Cu2O / CuO in the micro-arc oxidation film layer for changing the copper valence state prepared in this embodiment reaches 3.86, the hardness of the film layer reaches 802Hv, the roughness (Ra) reaches 0.598, and the thickness of the film layer is 20μm to 30μm.

[0059] Example 5

[0060] The Cu2O copper-based material was prepared using 2024 aluminum alloy as the substrate: the polished and cleaned aluminum alloy sheet was used as the anode, and the stainless steel container was used as the cathode. A pulsed AC power supply was used to perform a unidirectional and then bidirectional micro-arc oxidation treatment. The anode of the aluminum alloy workpiece was immersed in the working liquid, and then bipolar pulse electricity was applied to both the cathode and the anode, with a forward voltage of 500V, a negative voltage of 90V, a pulse width of 2000ms, and an interval of 500ms. The Cu2O copper-based material was obtained by treating at a temperature above 20°C for 20 minutes.

[0061] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the concentration of sodium hydroxide in the working solution is 2 g / L, the concentration of sodium silicate is 5 g / L and the concentration of nano copper oxide is 12 g / L.

[0062] The aluminum alloy is 2024 aluminum alloy, and the size is 20 mm×20 mm×2 mm.

[0063] Before the micro-arc oxidation treatment, the electrolyte was stirred for 30 minutes by a magnetic stirring pump at a speed of 1500 rad / min to ensure that the nano-CuO particles were evenly dispersed and formed a stable colloid with a negative Zeta potential.

[0064] The initial water temperature in this embodiment is 20°C.

[0065] XPS analysis of the Cu2O copper-based material micro-arc oxidation film prepared in this example is as follows Figure 2 As shown in the figure, according to the fitting results, the integral area of ​​copper in different valence states is calculated to obtain a relative content of Cu2O / CuO of 4.65. The hardness of the film layer reaches 762Hv, the roughness (Ra) reaches 1.861, and the film layer thickness is 50μm to 60μm, as measured by an eddy current thickness gauge. Figure 3 shown.

[0066] Example 6

[0067] The difference between this embodiment and embodiment 5 is that the forward voltage is 600V, and the other implementation conditions are the same.

[0068] The relative content of Cu2O / CuO in the Cu2O copper-based material micro-arc oxidation film prepared in this embodiment reaches 5.21, the hardness of the film reaches 862Hv, the roughness (Ra) reaches 2.281, and the thickness of the film is 50μm-60μm. It can be seen that the content of Cu2O is increased by adjusting the forward voltage.

[0069] Example 7

[0070] The difference between this embodiment and embodiment 5 is that the negative voltage is 110V, and other implementation conditions are the same.

[0071] The relative content of Cu2O / CuO of the micro-arc oxidation film layer for changing the copper valence state prepared in this embodiment reaches 12.87, the hardness of the film layer reaches 815Hv, the roughness (Ra) reaches 2.065, and the thickness of the film layer is 45μm-55μm. It can be seen that by adjusting the negative voltage, the content of Cu2O is increased.

[0072] Example 8

[0073] The difference between this embodiment and embodiment 5 is that the negative voltage is 160V, and the other implementation conditions are the same. The film layer prepared in this embodiment is not fully grown. Figure 4 As shown. It can be seen that when the negative voltage is too large, a complete film layer cannot be generated.

[0074] Example 9

[0075] The Cu2O copper-based material was prepared using 2024 aluminum alloy as the substrate: the polished and cleaned aluminum alloy sheet was used as the anode, and the stainless steel container was used as the cathode, and a pulsed AC power supply was used for unidirectional micro-arc oxidation. The anode of the aluminum alloy workpiece was immersed in the working liquid, and then bipolar pulse electricity was applied to both the cathode and the anode, with a forward voltage of 560V, a pulse width of 2000ms, and an interval of 1000ms. The Cu2O copper-based material was obtained after the treatment for 25 minutes at a temperature above 20°C.

[0076] The working solution is a mixture of deionized water, alkaline hydroxide, silicate and nano copper oxide particles; the working solution has a hydroxide concentration of 3 g / L, a silicate concentration of 8 g / L and a nano copper oxide concentration of 10 g / L.

[0077] The relative content of Cu2O / CuO in the micro-arc oxidation film for changing the copper valence state prepared in this embodiment reaches 0.17, the hardness of the film reaches 300Hv, and the roughness (Ra) reaches 0.213. The film thickness is 10μm to 20μm. Under the condition of no negative voltage, the relative content of Cu2O is low.

[0078] For any technician familiar with the art, without departing from the scope of the technical solution of the present invention, the technical content disclosed above can be used to make many possible changes and modifications to the technical solution of the present invention, or modified into equivalent embodiments with equivalent changes. Therefore, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention should still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A micro-arc oxidation film layer capable of controlling the generation of cuprous oxide, characterized in that: A film layer is formed on the surface of a metal or alloy by micro-arc oxidation, wherein the porous structure of the film layer is filled with a mixture of CuO and Cu2O, wherein the Cu2O is obtained by high-temperature decomposition at 700°C-2000°C during micro-arc oxidation discharge and reduction reaction in a negative process; preferably, the film layer has a thickness of 10 μm to 70 μm.

2. The micro-arc oxidation film layer capable of controlling the generation of cuprous oxide according to claim 1, characterized in that: By controlling the forward voltage and the negative voltage during the micro-arc oxidation process, the contents of CuO and Cu2O are regulated.

3. The micro-arc oxidation film layer capable of controlling the generation of cuprous oxide according to claim 1, characterized in that: The forward voltage is 200V-700V to generate Cu2O phase; the negative voltage is 50V-150V to promote the reduction of CuO to Cu2O and increase the relative content of Cu2O; preferably, the forward voltage is 500V-600V, and the negative voltage is 90V-110V.

4. The micro-arc oxidation film layer capable of controlling the generation of cuprous oxide according to claim 1, characterized in that: The metal or alloy includes aluminum, magnesium, titanium, aluminum alloy, magnesium alloy, titanium alloy; preferably, the aluminum alloy is 2024 aluminum alloy, 7075 aluminum alloy or 6061 aluminum alloy.

5. The method for preparing a micro-arc oxidation film capable of controlling the generation of cuprous oxide according to any one of claims 1 to 4, characterized in that: The preparation method uses micro-arc oxidation to treat a metal or aluminum alloy substrate to form a film layer on the surface of the substrate; the electrolyte of the micro-arc oxidation includes water, alkaline hydroxide, silicate, and nano CuO particles; the micro-arc oxidation uses the metal or aluminum alloy substrate as an anode and a stainless steel container as a cathode, uses a pulsed AC power supply for treatment, and has a forward voltage of 200V-700V, a negative voltage of 50-150V, a pulse width of 200ms-4000ms, an interval between pulses of 200ms-1000ms, a temperature of 20°C-85°C, and a treatment time of 2min-30min; preferably, the forward voltage is 500V-600V, the negative voltage is 90V-110V, the pulse width is 1000ms-3000ms, and the interval between pulses is 250ms-750ms.

6. The preparation method according to claim 5, characterized in that: The mass concentration of alkaline hydroxide is 1g / L-15g / L, the mass concentration of silicate is 1g / L-25g / L, and the mass concentration of nano CuO particles is 0.1g / L-20g / L; the alkaline hydroxide includes one or more of potassium hydroxide and sodium hydroxide; the silicate includes one or more of sodium silicate and potassium silicate; the size of the nano copper oxide particles is 1nm-100nm; and the pH value of the electrolyte is 8-14.

7. The preparation method according to claim 5, characterized in that: The power supply is a bipolar pulse power supply, which adopts a unidirectional mode or a unidirectional first and then bidirectional working mode.

8. A method for improving the bactericidal and antibacterial stability of Cu2O, characterized in that: The method according to any one of claims 5 to 7 is used to form a film layer on the surface of the substrate, so that the porous structure of the film layer is filled with a mixture of CuO and Cu2O.

9. A method for regulating the valence state of copper oxide in a micro-arc oxidation film, characterized in that: The method according to any one of claims 5 to 7 is adopted, and the valence state of copper oxide is controlled by controlling the forward voltage and the negative voltage, so as to adjust the relative content of Cu2O / CuO.

10. Use of the Cu2O copper-based material according to claim 1 in microsurgical instrument materials, orthopedic external fixator materials, and thoracic surgical instrument materials.

Citation Information

Patent Citations

  • Surface treatment method of aluminum alloy shuttle for spinning and wear resistant shuttle

    CN106702454A

  • Preparation method of antibacterial wear-resistant coating on surface of titanium implant material

    CN112981493A

  • Preparation method and application of in-situ growth carbon dioxide electroreduction electrocatalyst

    CN117127207A

  • The formation method of porous antibacterial coatings on titanium and titanium alloys surface

    EP3757257A1